Synergistic Effect of Pyrvinium Pamoate and Azoles Against Aspergillus fumigatus in vitro and in vivo - Sun, Yi (Front Microbiol, 2020)
The effects of pyrvinium pamoate alone and in combination with azoles [itraconazole (ITC), posaconazole (POS), and voriconazole (VRC)] were evaluated against Aspergillus fumigatus both in vitro and in vivo. A total of 18 clinical strains of A. fumigatus were studied, including azole-resistant isolates harboring the combination of punctual mutation and a tandem repeat sequence in the Cyp51A gene (AFR1 with TR34/L98H and AFR2 with TR46/Y121F/T289A). The in vitro results revealed that pyrvinium individually exhibited minimal inhibitory concentration (MIC) of 2 μg/ml against AFR1 but was ineffective against other tested strains (MIC > 32 μg/ml). Nevertheless, the synergistic effects of pyrvinium with ITC, VRC, or POS were observed in 15 [83.3%, fractional inhibitory concentration index (FICI) 0.125–0.375], 11 (61.1%, FICI 0.258–0.281), and 16 (88.9%, FICI 0.039–0.281) strains, respectively, demonstrating the potential of pyrvinium in reversion of ITC and POS resistance of both AFR1 (FICI 0.275, 0.281) and AFR2 (FICI 0.125, 0.039). The effective MIC ranges in synergistic combinations were 0.25–8 μg/ml for pyrvinium, 0.125–4 μg/ml for ITC, and 0.125 μg/ml for both VRC and POS, demonstrating 4- to 32-fold reduction in MICs of azoles and up to 64-fold reduction in MICs of pyrvinium, respectively. There was no antagonism. The effect of pyrvinium–azole combinations in vivo was evaluated by survival assay and fungal burden determination in the Galleria mellonella model infected with AF293, AFR1, and AFR2. Pyrvinium alone significantly prolonged the survival of larvae infected with AF293 (P < 0.01) and AFR1 (P < 0.0001) and significantly decreased the tissue fungal burden of larvae infected with AFR1 (P < 0.0001). Pyrvinium combined with azoles significantly improved larvae survival (P < 0.0001) and decreased larvae tissue fungal burden in all three isolates (P < 0.0001). Notably, despite AFR2 infection was resistant to VRC or pyrvinium alone, pyrvinium combined with VRC significantly prolonged survival of both AFR1 and AFR2 infected larvae (P < 0.0001). In summary, the preliminary results indicated that the combination with pyrvinium and azoles had the potential to overcome azole resistance issues of A. fumigatus and could be a promising option for anti-Aspergillus treatment.